Digital health intervention in an innovative and personalized approach to the management of irritable bowel syndrome in Indian patients: A case series (Indian Journal of Case Reports, 2025)
Irritable bowel syndrome (IBS) is a chronic gastrointestinal disorder marked by abdominal discomfort and altered bowel habits. Despite its prevalence, managing IBS remains challenging due to its complex nature. Digital health interventions have emerged as innovative solutions, combining dietary changes, psychological support, and wellness strategies. This case series of seven IBS patients explores the effectiveness of the DailyBloom IBS App in managing IBS through a 14-week program incorporating a low-FODMAP diet, cognitive behavioral therapy, and physical wellness. Patients experienced reduced abdominal pain, bloating, and diarrhea frequency, alongside the improved quality of life, including less anxiety and stress. This case series highlights the potential of digital therapeutics as a complement to conventional care in India. The DailyBloom™ IBS App adopts a structured four-phase approach: discovery (weeks 1–2), elimination (weeks 3–5), reintroduction (weeks 6–11), and sustenance (weeks 12–14). Patients, categorized into IBS subtypes (IBS-constipation, IBS-diarrhea, IBS-mixed, IBS-undefined), were evaluated for symptom progression, management, and outcomes. Findings emphasize the role of digital therapeutics in providing personalized, evidence-based care, marking a significant advancement in IBS management within the digital health landscape promising both symptom relief and lifestyle improvements for patients.